Actions to prevent school bullying in elementary school: an experience report in school/educational psychology (Research, Society and Development, 2022)
This article aims to share the experience and learning acquired in a university extension project with an emphasis on School/Educational Psychology. The actions were broadcast in a Municipal Public School in the city of Campina Grande-PB and had as target audience the students who attended elementary school. During the construction methodology of the use of the project, we searched for re-significations on bullying meiosis of the use of different projects, re(significations) on bullying Thus, in this work we relate two interventions implemented during the project, and in parallel we weave several studies on Bullying and its aspects in the elementary school universe.